Collapse Of Conical Shells Having Single Dimple Imperfection Under Axial Compression - Ifayefunmi, Olawale; Mahidan, Fairuz Mardhiah (American Society of Mechanical Engineers (ASME), 2021)
This paper aims to provide experimental results into the buckling behavior of cones having single dimple imperfection subjected to axial compression. Results of eight laboratory scaled conical test models and their accompanying numerical data are presented. Cones were manufactured in pairs with single dimple imperfection amplitude, A, of 0.0, 0.56,1.12, and 1.68. Experimental results reveal good repeatability of collapse load. The errors between each pair were found to be 3%, 7%, 11%, and 1%. Furthermore, the comparison between test data and the numerically predicted collapse load was seen to be good. The ratio of collapse test load to finite element predicted values are [(0.96, 0.99), (1.04, 1.10), (1.06, 0.94), (1.0, 1.01)]. The buckling of axially compressed conical shells using the single dimple imperfection type appears to be strongly influenced by: (i) the dimple/imperfection amplitude, (ii) the cone geometric parameter, i.e., radius-to-thickness ratio and cone angle, and (iii) the location of the dimple